Peningkatan Efektivitas Pembelajaran Kelas Studio Online Dengan Metode Studiogogi Modul S.O.L.E - Hanif Azhar (Cakrawala: Jurnal Pendidikan, 2021)
Interactive learning is one of the most challenging studio design class lecturers, especially in virtual learning classes. Interactive learning could activate the student’s participation during the studio class activity. This action research class aims to examine the effectiveness of an online design studio class with a Studio Oriented Learning Environment (S.O.L.E) module introduced in Malaysia in 2018. This research methods use the spiral model action research approach initiated by Kemmis & McTaggart. This article results from action research conducted in an online studio class, Industrial Product Design, Telkom University. The subject of this experiment was students in a required course in the design curriculum, Basic Studio Design class. The lecturer’s creativity is a fundamental requirement to lead this studio class success. The author found that the Studio Oriented Learning Environment (S.O.L.E) module successfully raised the students’ participation and understanding during a virtual class activity. This method could elevate the online learning effectiveness up to 51.8% in the School of Creative Industries, Telkom University.